THE ROLE OF NON-REGIONAL POWERS IN CENTRAL ASIAN WATER AND ENERGY NEXUS - KAYUMOV, Abdurasul; OMELCHENKO, Elena (CENTRAL ASIA AND THE CAUCASUS, 2014)
Water as the least regulated issue is currently one of the key security factors in Central Asia. Although some efforts are made to regulate water through the establishment of a regional water regime, yet it remains unresolved. It has been stated that the involvement of international actors can have a positive effect on the solution of the problem. The analysis in this article shows that non-regional powers do not necessarily play a positive role in Central Asia. The water and energy nexus are often used by external powers as a geopolitical tool to influence regional countries for own political and economic interests.